Arsitektur Sistem Informasi Kinerja Guru Berbasis IASP2020 dengan Metode Togaf Framework - Joko Risanto; Zaiful Bahri; Ibnu Daqiqil; Elfizar Elfizar (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
In the national education standards, there are four factors that determine the quality of schools, namely the characteristics of the students, the competence of the teachers, the learning process and the leadership of the principal. To obtain quality teacher competence, effective, efficient and transparent teacher management is needed in the management of teaching and education personnel. To improve the quality of education, the government through the National Accreditation Board for Schools/Madrasahs has prepared the 2020 Education Unit Accreditation Instrument (IASP) containing standard instruments to measure school quality. Schools can implement IASP2020 to continuously monitor the performance of each factor to ensure school quality. In the teacher competence factor, a fast and responsive information system is needed so that the quality of teacher performance can be detected immediately to help schools immediately make the right decisions, immediately find the solutions needed for their problems so that teacher quality continues to maintain its competence. The design uses the Open Group Architecture Framework which has been proven to be reliable in solving information system governance problems. The results of this study are in the form of a recommendation for a strategic information system design that is worthy of being developed for teacher management.